Dysphagia among elderly people: Its assessment and management [Yaşlilarda disfaji, disfajinin deǧerlendirilmesi ve yönetimi] - (:unkn) unknown (My University, 2003)
The literature suggests that 2 to 74% elderly people have some degree of dysphagia. Unrecognised and poorly managed dysphagia may lead to aspiration pneumonia; choking; dehydration; chronic malnutrition; decreased quality of life, and premature death. For that reason dysphagia must be accurately assessed and promptly intervened by the health care professionals. The recognition of symptoms indicative of impaired swallowing problem is essential for nurses. SOAP protocol is a valid instrument for nurses to assses elderly people' impaired swallowing because it is a comprehensive protocol to assess and manage clients with swallowing problem in long term care.